Investigation of psychological factors affecting the behavior of reducing the use of plastic bags (Case study: Hypermarkets in Mashhad) - Ava Heidari; Negar Fallahi; Ensyeh Saberi; Parnian Hadian; Asma Azari; Yeganeh Hervay; Negar Hasany; Alireza Khorakian; Nasrin Ghodrati (علوم محیطی)
Introduction: Free plastic bags have practical benefits for consumers but because of their non-biodegradability and additives, they have adverse effects on the environment. Therefore, in this study, the factors affecting people's intention and behavior for using plastic bags with the Theory of Planned Behavior and Structural Equation Modeling were investigated.Material and methods: A total of 360 customers in seven major hypermarkets in different areas of Mashhad responded to the questionnaire. Data were analyzed using IBM SPSS Statistic V.22 and AMOS 24 software. An extended model based on the Theory of Planned Behavior was introduced with the constructs including cognitive attitude, affective attitude, economic motivation, feedback, subjective norm, behavioral control, intention, and behavior to determine the factors influencing the behavior.Results and discussion: The results of this study showed that more than half of the respondents to the questionnaires were women and more than 30% of them were in the age group of 25-35 years. The effect of demographic information on the intention to reduce plastic bags in hypermarkets was examined by the ANOVA test. Only the age (p <0.001, df = 7, F = 3.6) and the type of job (p <0.001, df = 7, F = 3.5) had a significant effect on the intention. The fit indices of the structural model were as follows: Chi-squared test was equal to 254.3 with freedom of 106, the ratio of Chi-squared to a degree of freedom was equal to 2.4, IFI was equal to 0.9, CFI was equal to 0.9, NFI was equal to 89, and RMSEA was equal to 0.622. According to the standard, the fit of the model was appropriate. Findings of the structural equation model can describe the relationships between variables: cognitive attitude had a significant statistical effect on effective attitude; there was a statistical relationship between cognitive attitudes and norm. In addition, cognitive attitudes (p <0.001) had a negative effect on behavioral control. There was a positive and significant (p <0.001) relationship between economic motivation and norm (coefficient of 0.18). Also, there was a negative and significant (p <0.001) relationship between feedback and norm (coefficient 0.43). Besides, there was a positive and significant (p <0.001) relationship between feedback and behavioral control (coefficient 0.45). Cognitive attitude had a positive and significance (p< 0.05) effect (coefficient of 0.16) on intention to reduce plastic bags. The norm with a coefficient of 0.41 had a positive and significant effect (p <0.001) on the intention.Conclusion: The results showed that the structural equation model with appropriate fit could describe the relationships between variables. The main parameters of the Theory of Planned Behavior (attitude, subjective norms, and behavioral control) significantly describe the intention of using plastic bags. Adding new variables such as feedback and economic incentives to this theory will help determine other predictors of behavior. The norm is one of the most important variables that mediate the influence of other factors such as cognitive attitude, affective attitude, economic motivation, feedback, and behavioral control on intention to using a plastic bag. Although the economic incentive affects the intention to use free plastic bags, it is appropriate to use the intervention approach based on the model presented in this study to find a solution.